Daratumumab-based regimens are highly effective and well tolerated in relapsed or refractory multiple myeloma regardless of patient age: subgroup analysis of the phase 3 CASTOR and POLLUX studies - Mateos, Maria-Victoria; Spencer, Andrew; Nooka, Ajay K; Pour, Ludek; Weisel, Katja; Cavo, Michele; Laubach, Jacob P; Cook, Gordon; Iida, Shinsuke; Benboubker, Lotfi; Usmani, Saad Z; Yoon, Sung-Soo; et al. (Haematologica, 2020)
The phase 3 POLLUX and CASTOR studies demonstrated superior benefit of daratumumab plus lenalidomide/dexamethasone or bortezomib/dexamethasone in relapsed/refractory multiple myeloma. Efficacy and safety of daratumumab was analyzed according to age groups of 65 to 74 years and ≥75 years. Patients received ≥1 prior line of therapy. In POLLUX, patients received lenalidomide/dexamethasone ± daratumumab (16 mg/kg weekly, cycles 1-2; every two weeks, cycles 3-6; monthly until progression). In CASTOR, patients received eight cycles of bortezomib/dexamethasone ± daratumumab (16 mg/kg weekly, cycles 1-3; every three weeks, cycles 4-8; monthly until progression). Patients aged >75 years received dexamethasone 20 mg weekly. For patients aged ≥75 years in POLLUX (median follow-up: 25.4 months), daratumumab/lenalido-mide/dexamethasone prolonged progression-free survival versus lenalido-mide/dexamethasone (median: 28.9 versus 11.4 months; hazard ratio, 0.27; 95% confidence interval, 0.10-0.69; P=0.0042) and increased overall response rate (93.1% versus 76.5%; P=0.0740). Neutropenia was the most common grade 3/4 treatment-emergent adverse event (daratumumab: 44.8%; control: 31.4%). Infusion-related reactions occurred in 12 (41.4%) patients. For patients aged ≥75 years in CASTOR (median follow-up: 19.4 months), daratumumab/bortezomib/dexamethasone prolonged progression-free survival versus bortezomib/dexamethasone (median: 17.9 versus 8.1 months; hazard ratio, 0.26; 95% confidence interval, 0.10-0.65; P=0.0022) and increased overall response rate (95.0% versus 78.8%; P=0.1134). Thrombocytopenia was the most common grade 3/4 treatment-emergent adverse event (daratumumab: 45.0%; control: 37.1%). Infusion-related reactions occurred in 13 (65.0%) patients. Similar findings were reported for patients aged 65 to 74 years in both studies. Taken together, this subgroup analysis of efficacy and safety of daratumumab was largely consistent with the overall populations.
Keywords: lenalidomid; Bortezomib; Lenalidomide; dexamethason; monoklonální protilátky; Antibodies, Monoclonal; Aged; lidé; bortezomib; mnohočetný myelom; senioři; Dexamethasone; Multiple Myeloma; Antineoplastic Combined Chemotherapy Protocols; Humans; protokoly protinádorové kombinované chemoterapie